Legal Consequences of an Unregistered Marriage Agreement From a Marriage Agreement Deed Canceled by The Supreme Court (Case Study of Marriage in The Decision of The Supreme Court Number 598/PK/PDT/2016) - Handayani, Widya Anggayesti; Djajaputra, Gunawan (Journal of Law, Politic and Humanities, 2024)
In Indonesia, a marriage agreement is regulated in Article 119 of the Civil Code and Article 29 of Law Number 1 Year 1974 concerning marriage. The marriage agreement is made by a notary as an authorized party and legalized by the marriage registrar. However, there are often problems related to marriage agreements, especially when they are not recorded by the marriage registrar. Meanwhile, the recording of a marriage agreement has an important urgency for each party, which provides justice, certainty, and legal benefits. The non-recording of a marriage agreement by a marriage registration officer will have legal consequences, one of which is the potential for legal problems that lead to disputes over joint property after divorce. This research analyzes how the importance of recording a marriage agreement and its legal consequences through Supreme Court Decision Number 598 PK/Pdt/2016 with a normative juridical approach. The results show that the marriage agreement can still be canceled because it does not meet the formal requirements of the provisions of Article 29 paragraph (1) of the Marriage Law, namely the element of being legalized by a marriage registration officer. The legal effect is that the assets obtained during the marriage must be separated and divided equally.